2018
DOI: 10.1007/s10126-018-9807-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Extracellular Matrix Synthesis by Shell Extracts from the Marine Bivalve Pecten maximus in Human Articular Chondrocytes— Application for Cartilage Engineering

Abstract: The shells of the bivalve mollusks are organo-mineral structures predominantly composed of calcium carbonate, but also of a minor organic matrix, a mixture of proteins, glycoproteins, and polysaccharides. These proteins are involved in mineral deposition and, more generally, in the spatial organization of the shell crystallites in well-defined microstructures. In this work, we extracted different organic shell extracts (acid-soluble matrix, acid-insoluble matrix, water-soluble matrix, guanidine HCl/EDTA-extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Various supplements are also described as simply playing an antioxidant role, such as glycosaminoglycans, frankincense, plant flavonoids and bioflavonoids [ 66 , 67 , 68 , 69 , 70 ]. On the contrary, we had previously shown that shell extracts of marine origin promote the catabolic pathway of human dermal fibroblasts, or the activity of MMP-1 in chondrocytes [ 71 , 72 ]. Nevertheless, the composition of the Promerim ® is very different from shell extracts—it does not contain high concentrations of marine minerals.…”
Section: Discussionmentioning
confidence: 99%
“…Various supplements are also described as simply playing an antioxidant role, such as glycosaminoglycans, frankincense, plant flavonoids and bioflavonoids [ 66 , 67 , 68 , 69 , 70 ]. On the contrary, we had previously shown that shell extracts of marine origin promote the catabolic pathway of human dermal fibroblasts, or the activity of MMP-1 in chondrocytes [ 71 , 72 ]. Nevertheless, the composition of the Promerim ® is very different from shell extracts—it does not contain high concentrations of marine minerals.…”
Section: Discussionmentioning
confidence: 99%
“…However, the quality of the in vitro synthesized cartilage organoid is not strictly identical to healthy hyaline cartilage in vivo. We have previously shown that treatment with Pecten maximus extracts on monolayer cultures of chondrocytes or cartilaginous organoids promotes chondrocyte redifferentiation and phenotype maintenance [ 61 ]. In this context, Promerim ® is a good treatment for promoting hyaline-like ECM production and improving differentiation, as recently demonstrated for equine articular chondrocytes (eACs) [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many nutraceuticals have an antioxidant effect or promote the synthesis of prostaglandin E2 (PGE2) and LT4 pro-inflammatory factors [ 64 , 65 , 66 , 67 ]. We have demonstrated that shell extracts of marine origin increase MMP-1 activity in HACs as well as the catabolism of human dermal fibroblasts [ 61 , 68 ]. However, such effects may be different for Promerim ® hydrolysates due to their qualitative nature, because shell extracts contain high concentrations of marine minerals.…”
Section: Discussionmentioning
confidence: 99%
“…SOM proteins (SOMPs) embedded within the mineral are hypothesized to serve as a framework for crystal nucleation [reviewed by [ 16 ]. The proteins involved in the process of skeletal biomineralization have been described and studied extensively in echinoderms [e.x., 17 , 18 ] [and reviewed by [ 19 , 20 ], mollusks [e.x., 21 24 ] and mammals [e.x., 25 27 ], among others [ 28 ]. At present, the best described SOMP complex is of mammalian bone and teeth [ 15 ].…”
Section: Introductionmentioning
confidence: 99%